S14 Physiotherapists' opinions of the physiotherapy assessment of Breathing Pattern Dysfunction: a qualitative study. (11th November 2022) - Grillo, L; Lewis, A; Shannon, H; Russell, AM
Abstract : Introduction: Breathing Pattern Dysfunction (BPD) describes individuals whose breathing pattern is not aligned with their respiratory or metabolic requirements, resulting in breathlessness, air hunger and reduced quality of life. 1 Physiotherapy assessment is essential to ensure that patients can access effective therapy. Currently, there are no best practice guidelines to inform physiotherapists of the essential components for BPD assessments. 2 Objectives: Evaluate clinicians' preferred descriptors for BPD Describe the components frequently included in a patient assessment Explore physiotherapists' understanding of the assessment of BPD Methods: A 24-item survey was developed and distributed via social media and emailed to UK specialist physiotherapy interest groups. Two semi-structured focus groups, including open-ended discussion points, were subsequently completed with 15 specialist physiotherapists. Survey information was collated as percentages and focus groups transcribed verbatim before a thematic analysis was completed. Results: 103 physiotherapists completed the survey, which identified a lack of consensus in how to define BPD, but some agreement on the components to include in assessment ( figure 1 ). Three main themes resulted from the focus groups. Participants expressed frustration with inconsistency of terms used to describe the condition (1. Nomenclature and Language) and felt that BPD sat within the broader concept of breathlessness as an important component of breathlessness assessment (2. BPD and Breathlessness). The importance of physiotherapy assessment was discussed as being an important part of the therapy and recovery itself (3. Value of assessment). Assessment of BPD was discussed as a specialist skill, and important in patients' validation of their symptoms. However, there was lack of agreement of the assessment methods and importance of diaphragm assessment. Conclusion: This novel qualitative clinician-focused investigation of BPD assessment provides valuable insights into physiotherapists' assessment preferences and will be important when designing clinical practice guidance for BPD Assessment. Patient perceptions will provide a deeper understanding of BPD and its assessment. References: Vidotto LS, Carvalho CRF de, Harvey A, Jones M. Dysfunctional breathing: what do we know? Jornal Brasileiro de Pneumologia 2019;45 (1). Todd S, Walsted ES, Grillo L et al . Novel assessment tool to detect BPD in patients with refractory asthma. Respirology 2018;23 (3).